2005
DOI: 10.1097/01.rct.0000179243.54977.3f
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Myocarditis Depicted by Cardiac Magnetic Resonance Imaging

Abstract: Giant cell myocarditis is a rare condition, the cardiac magnetic resonance imaging findings of which have not been previously described. The disease usually occurs in young previously healthy people and is typified by rapidly progressive cardiac dysfunction, often requiring cardiac transplantation. A case of giant cell myocarditis is presented, with associated pathologic and imaging findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…9 However, EMB is indicated when the suspicion of giant cell myocarditis arises (reported sensitivity ranges between 82% and 85%), as this entity is frequently fatal from progressive cardiac failure or arrhythmias and can be ameliorated by immunosuppressive therapy and/or cardiac transplantation. 10,11 In a recent prospective study of biopsy-proven myocarditis, Caforio et al 12 identified giant cell myocarditis, in addition to biventricular failure, as one of the predictors of death/transplantation. Despite the aforementioned limitations, EMB is still considered the gold standard for the exclusion or diagnosis of suspected myocarditis.…”
Section: Endomyocardial Biopsymentioning
confidence: 98%
“…9 However, EMB is indicated when the suspicion of giant cell myocarditis arises (reported sensitivity ranges between 82% and 85%), as this entity is frequently fatal from progressive cardiac failure or arrhythmias and can be ameliorated by immunosuppressive therapy and/or cardiac transplantation. 10,11 In a recent prospective study of biopsy-proven myocarditis, Caforio et al 12 identified giant cell myocarditis, in addition to biventricular failure, as one of the predictors of death/transplantation. Despite the aforementioned limitations, EMB is still considered the gold standard for the exclusion or diagnosis of suspected myocarditis.…”
Section: Endomyocardial Biopsymentioning
confidence: 98%
“…The presence of multinucleated giant cells on hematoxylin and eosin staining of endomyocardial biopsy samples is the pathologic hallmark of this entity as shown in Figures 1 and 2 from our own patient in this reported case. Although MRI is not sensitive enough to rule out GCM, it assists in the diagnosis by depicting areas of involvement and directing the necessary biopsy [10,11]. MRI also aids in the exclusion of other types of cardiomyopathy and provides quantitative measures of right and left ventricular function for assessing disease progression and prognosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Current attempts to improve diagnostic accuracy include screening for viral RNA in EMBs 16, 17 , serum anti-heart autoantibodies 16 , and use of magnetic resonance imaging (MRI) 18, 19 . Transcriptomics has emerged as highly valuable tool for complex pathologic diagnosis.…”
Section: Introductionmentioning
confidence: 99%